2009
DOI: 10.1136/jme.2009.029264
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of patients’ motivations for their participation in genetics-related research

Abstract: We discuss the distinction drawn between motives for research participation focused upon self (personal) and others (familial/social), and observe that personal, social and familial motives can be seen as interdependent. For example, research participation that is undertaken to benefit others, particularly relatives, may also offer a number of personal benefits for self, such as enabling participants to feel that they have discharged their social or familial obligations. We argue for the need to move away from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 29 publications
10
115
2
Order By: Relevance
“…Understanding what influenced their decision to engage and what they prospectively felt they may gain from the process (or, indeed, what potential costs they perceived) may have provided a useful comparison or contrast to the later reflections on experience. While it had previously been assumed that research participation primarily stemmed from a sense of altruism (Hallowell et al, 2010), more recent research has identified nuance and complexity in this decision and action and acknowledge personal, social and familial motivations. More recently, Sikweyiya and Jewkes (2013) have explored the interaction between altruism and self-interest and conclude the decision to participate is due to a careful consideration of the costs and benefits to themselves, as well as to others.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding what influenced their decision to engage and what they prospectively felt they may gain from the process (or, indeed, what potential costs they perceived) may have provided a useful comparison or contrast to the later reflections on experience. While it had previously been assumed that research participation primarily stemmed from a sense of altruism (Hallowell et al, 2010), more recent research has identified nuance and complexity in this decision and action and acknowledge personal, social and familial motivations. More recently, Sikweyiya and Jewkes (2013) have explored the interaction between altruism and self-interest and conclude the decision to participate is due to a careful consideration of the costs and benefits to themselves, as well as to others.…”
Section: Discussionmentioning
confidence: 99%
“…Patients motivations for trial involvement are multifaceted and complex, 469 and include a range of personal and social elements. 470 Patients often stated altruistic reasons and expressed the desire to help others by contributing to the furthering of clinical knowledge.…”
Section: Trial Involvementmentioning
confidence: 99%
“…25 Yet, in a study of reasons underlying donating cancer tissue in New South Wales, Australia, FIG. 3.…”
Section: Discussionmentioning
confidence: 98%